Pessimism and overcommitment: An online experiment with tempting YouTube content - Claes Ek; Margaret Samahita (University College Dublin, UCD School of Economics, 2022)
This paper explores the possibility that demand for costly commitment may prove unnecessary and thus excessive. In an online experiment, subjects face a tedious productivity task where tempting YouTube videos invite procrastination. Subjects can pay for a commitment device that removes the videos with some probability less than one, allowing us to compare their willingness to pay with realized material and psychological costs of temptation. A significant share of subjects overestimate their commitment demand, being overly pessimistic about their performance when tempted. However, the total realized ex-post disutility from undercommitment is greater than that from overcommitment.
Keywords: C91; D03; D91; 330; Commitment devices; pessimism; self-control